Masseteric haemangioma in old age-a rare presentation - Kumari, Rakhi (International Journal of Research in Medical Sciences, 2016)
Intramuscular haemangioma is a rare benign congenital neoplasm accounting for <1% of all haemangioma. It affects mainly the trunk and the extremities, where the muscle volume is larger. The masseter muscle is the most frequently involved site in the head and neck area accounting for 5% of all intramuscular haemangioma. Most cases of intramuscular haemangioma occur before third decade of life and its occurrence in old age is a rare finding.